2015
DOI: 10.3109/10428194.2014.981172
|View full text |Cite
|
Sign up to set email alerts
|

ABT-199, a BH3 mimetic that specifically targets Bcl-2, enhances the antitumor activity of chemotherapy, bortezomib and JQ1 in “double hit” lymphoma cells

Abstract: Double hit lymphoma (DHL) is a recently recognized lymphoma with a survival of less than 2 years. Both ABT-737, a Bcl-2/Bcl-XL inhibitor, and ABT-199, which selectively targets Bcl-2, were potently cytotoxic against DHL cell lines Sc-1 and OcI-LY18, the RL cell line and primary human DHL cells, but not Ramos cells, which lack Bcl-2 expression. ABT-199 was more potent than ABT-737, and is the most promising of the BH3 mimetics to date. The DHL cell lines were also sensitive (< 200 nM) to doxorubicin, methotrexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 20 publications
6
46
0
1
Order By: Relevance
“…80 Combination of venetoclax with doxorubicin or cytarabine, bortezomib, and JQ1 produced synergistic cell kill against the double-hit lymphoma cell lines cultured in vitro. 81 In vitro and in vivo results also supported that radiotherapy could synergize with venetoclax for treatment of DLBCL and MCL. 82 All the above studies provide evidence for the feasibility of future combination therapy options.…”
supporting
confidence: 55%
“…80 Combination of venetoclax with doxorubicin or cytarabine, bortezomib, and JQ1 produced synergistic cell kill against the double-hit lymphoma cell lines cultured in vitro. 81 In vitro and in vivo results also supported that radiotherapy could synergize with venetoclax for treatment of DLBCL and MCL. 82 All the above studies provide evidence for the feasibility of future combination therapy options.…”
supporting
confidence: 55%
“…In both models, the degree of apoptosis induction in tolerant cells cotreated with CPI203 and ABT-737 was comparable with parental cells treated with BETi alone, suggesting that pharmacologic inhibition of BCL2 family members can abrogate tolerance to BETi. Notably, combination of the BET inhibitor JQ1 with ABT-199 showed synergistic effects on growth inhibition (13), highlighting the potential of combining BETi with BH3 peptidomimetics.…”
Section: Resultsmentioning
confidence: 99%
“…Both Bcl-2 and Bcl-X L function to dampen the apoptotic response by hindering Bax-Bak mediated perforation of the mitochondrial outer membrane, thus preventing cytochrome-c release and activation of the caspase cascade. Several groups have reported that the anti-tumour effect of bortezomib is greatly enhanced by antagonists of Bcl-2 function (Johnson-Farley et al, 2015;Kunami et al, 2014;Paoluzzi et al, 2008;Reuland et al, 2012). The Bcl-2 inhibitors ABT-737 and ABT-199 respectively enhance the cytotoxicity of bortezomib in adult T-cell leukaemia/lymphoma (Kunami et al, 2014) and "double hit" lymphoma cells (Johnson-Farley et al, 2015).…”
Section: Mechanisms Of Resistance To Bortezomib and Other Inhibitors mentioning
confidence: 99%